Pearly penile papule: athypical clinical presentation in a child - Peixoto, Amanda Brraga; Tostes, Camilee P.; Santos, Hilda Maria P.A.; Bartolini, Renata J.; Modesto, Paula B.; Nery, José Augusto C. (Brazilian Journal of Sexually Transmitted Diseases, 2010)
Introduction: pearly penile papules (PPPs), also known as Tyson’s glands, are a type of angiofibroma; thus, benign lesions. They are characterized by asymptomatic pearly white papules, located on the glans penis, most often in postpubertal males. They do not require any treatment other than reassurance. At this work, we present a case of PPP with athypical localization, age and symptomathology, showing the importance of the clinical distinction with human papillomavirus (HPV) and other diseases, and the histopathologic exam on uncertain diagnosis lesions.